|aCorruption and productivity |bFirm-level evidence from the BEEPS survey - Donato De Rosa; Nishaal Gooroochurn; Holger Görg (The World Bank, 2010)
Using enterprise data for the economies of Central and Eastern Europe and the Commonwealth of Independent States, this study examines the effects of corruption on productivity. Corruption is defined as a 'bribe tax' and is compared with another form of institutional inefficiency, which is often believed to be closely linked with corruption: the 'time tax' imposed on firms by red tape. When testing their effects in the full sample, only the bribe tax appears to have a negative effect on firm-level productivity, while the effect of the time tax is insignificant. At the same time, there is no evidence of a trade-off between the time and the bribe taxes, implying that bribing does not emerge as a second-best option to achieve higher productivity by helping circumvent cumbersome bureaucratic requirements. When the sample is split between European Union and non-European Union countries, the time tax turns out to have a negative effect only in European Union countries and the bribe tax only in non-European Union countries. This suggests that the institutional environment influences the way in which firm behavior affects firm performance. In particular, the impact of bribing for individual firms appears to vary depending on overall institutional quality: in countries where corruption is more prevalent and the legal framework is weaker, bribery is more harmful for firm-level productivity.
hdl:10986/4000
Keywords: 330